Digital Activism in Social Movements and Its Influence on the Implementation of State Administration in Indonesia - Krismiyati Krismiyati; Irwan Abdu Nugraha; Myristica Imanita; Satryo Sasono; Fakhry Amin (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The existence of digital platforms provides a new space for people to interact. In this case, interaction in the form of activism also takes advantage of the role of technology in carrying out social movements. This social movement can then influence how the implementation of state administration in Indonesia is carried out. This research then examines how digital activism through social movements affects state administration in Indonesia. This type of research is descriptive qualitative research. The data used in this study comes from various research results and previous studies, which still have relevance to the contents of this research. The results of this study then found that the emergence of technology caused many people to become literate in the world of activism. This causes many changes in the dynamics of the Indonesian state, especially in politics. The emergence of digital activism has led to the need for various changes in regulations and administrative regulations in Indonesia.